El Salvador : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for El Salvador. (IMF Staff Country Reports; Country Report ;, 2009)
El Salvador's 2008 Article IV Consultation examines the country's economic developments and policies. In 2007, the fiscal position improved, the public debt-to-GDP ratio declined, and economic growth reached its highest level in a decade. The rise in global commodity prices has also generated substantial inflation pressures. The stock of bank deposits has stagnated relative to end-2007, while deposit rates have increased slightly. Interbank repo rates have also risen recently, reflecting tighter funding conditions, and banks have increased their external borrowing, in part to build up liquidity.